Validating the Patient‐Reported Outcomes Measurement Information System Short Form v1.0–Anxiety 8a in a sample of young adult cancer survivors: Comparison with a structured clinical diagnostic interview. Issue 19 (1st July 2021) - Recklitis, Christopher J.; Blackmon, Jaime E.; Chevalier, Lydia L.; Chang, Grace
Abstract : Background: The objective of this study was to validate the Patient‐Reported Outcomes Measurement Information System Short Form v1.0–Anxiety 8a (PROMIS‐A‐SF) against a structured diagnostic interview in order to determine its accuracy and the most appropriate cutoff score for identifying anxiety disorders in young adult cancer survivors (YACSs). Methods: Two hundred forty‐nine YACSs aged 18 to 40 years (50% male) completed the PROMIS‐A‐SF and the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (SCID). The SCID was used to determine whether participants met the criteria for an anxiety diagnosis. Receiving operator characteristic analyses were performed to determine the concordance of the PROMIS‐A‐SF and the SCID as well as cutoff scores with sensitivity (≥0.85) and specificity (≥0.75) appropriate for an anxiety screening measure. Results: The PROMIS‐A‐SF was determined to have good overall discrimination in comparison with the SCID (area under the curve, 0.84). A PROMIS‐A‐SF t ‐score cutoff ≥ 53.2 (total predictive value, 67.9%) came closest to meeting the study criteria with a sensitivity of 88%, but the specificity was only 65%. In a hypothetical screening example, this cutoff led to moderate levels of missed cases (14%) and a significant proportion of clinical referrals that were unnecessary by SCID criteria (35%). Of the survivors referred for services according to these criteria, less than one‐third (29%) would have a SCID anxiety diagnosis. Conclusions: The PROMIS‐A‐SF demonstrated moderately strong concordance with anxiety disorders measured by the SCID, but cutoff scores did not meet study criteria for clinical screening. Although it may not be appropriate as a standalone screener, the PROMIS‐A‐SF may be useful for assessing anxiety in YACSs when it is incorporated into clinical practice or when it is combined with other measures. Abstract : The Patient‐Reported Outcomes Measurement Information System Short Form v1.0–Anxiety 8a (PROMIS‐A‐SF) demonstrates good overall concordance with anxiety disorders identified by a structured diagnostic interview in a sample of 249 young adult cancer survivors. Although no cutoff scores demonstrate sensitivity and specificity appropriate for clinical screening, the PROMIS‐A‐SF may be useful when it is incorporated into clinical practice or when it is combined with other measures.